Challenges with New Age Digital Startups - Kukreja, Nitin (Digital Repository of Theses, 2023)
n recent times, there has been a significant surge in the popularity of the terms "digital transformation" and "startup." Considering the ongoing digital transition, this research proposal aims to investigate the key factors that contribute to the success of startups. To provide a comprehensive understanding of digital transformation, the proposal begins by defining the concept and explaining its operational mechanisms. Startups have traditionally achieved success in the business sector by introducing disruptive innovations. However, it remains a challenge to discern how startups differ from more established businesses in terms of strategy, management, and organizational structure. This study recognizes the potential drawbacks that may arise during the digital transition, which are discussed in the final section. The primary objective of this research proposal is to help readers comprehend the distinct benefits that digital transformation can offer to startups. Additionally, this study aims to identify the specific challenges that startups face in adopting project management practices, particularly within the digital or information technology industry. By examining various project management techniques employed by startups, the desired outcome of this study is to showcase how startups develop project management approaches and address associated issues.